Software engineering: rekayasa perangkat lunak - Ian Sommerville (Erlangga, 2003)
ast jil.2 = c.1-4/oen, jil.2=c.5/oen, jil.1=c.1/ast jil.1 =c.2/ast jil.1 =c.3-5/ast jil.2 =c.6/ast, jil.1 =c.6/ast jil.2 =c.7/stoc5.jil.1=c1-6,jil.2=c1-7